Visual Health Education: A Creative Campaign Through Infographic Design Training Using Canva for High School Students - Anwarudin Anwarudin; Arum Nuryati (Devotion : Journal of Research and Community Service, 2026)
Visual Health Education: A Creative Campaign Through Infographic Design Training Using Canva For High School Students explores health education for high school students, which requires a communicative and creative approach aligned with the characteristics of the digital generation. One strategy that can be applied is a visually based health campaign through infographic design training using Canva. This study aims to describe the implementation of health infographic design training using Canva and analyze its contribution to improving students’ health understanding, digital literacy, and visual communication creativity. This study used a descriptive qualitative approach with a participatory training approach. The activities were carried out through stages including identifying needs, delivering health-related materials, introducing infographic design principles, practicing the use of Canva, assisting with product development, and presenting the results of visual campaigns. Data were collected through observation, documentation of student work, participant reflections, and brief interviews. The results showed that Canva-based infographic design training increased student engagement in understanding health issues, primarily because the information was presented in a simple, engaging, and easily shareable format. Students acted not only as recipients of information but also as creators of health messages, able to process data, construct visual narratives, and convey preventive advice to their peers. These findings confirm that visually based health education can be an innovative strategy in school health promotion while strengthening students’ digital literacy and creative communication skills.